2021
DOI: 10.3389/fpls.2021.688187
|View full text |Cite
|
Sign up to set email alerts
|

The Lotus japonicus NPF3.1 Is a Nodule-Induced Gene That Plays a Positive Role in Nodule Functioning

Abstract: Nitrogen-fixing nodules are new organs formed on legume roots as a result of the beneficial interaction with the soil bacteria, rhizobia. Proteins of the nitrate transporter 1/peptide transporter family (NPF) are largely represented in the subcategory of nodule-induced transporters identified in mature nodules. The role of nitrate as a signal/nutrient regulating nodule functioning has been recently highlighted in the literature, and NPFs may play a central role in both the permissive and inhibitory pathways co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…CoNPF3.1 (40839_c0_g1) is annotated into the nitrate transporter1/peptide transporter (NPF) family, and it has been described as transmembrane transporter, gibberellic acid homeostasis, and nitrate assimilation in Arabidopsis thaliana [ 21 ] . It may improve the development of buds and the growth of roots [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…CoNPF3.1 (40839_c0_g1) is annotated into the nitrate transporter1/peptide transporter (NPF) family, and it has been described as transmembrane transporter, gibberellic acid homeostasis, and nitrate assimilation in Arabidopsis thaliana [ 21 ] . It may improve the development of buds and the growth of roots [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…In L. japonicus , an in silico analysis showed that the expression of eight LjNPF genes was upregulated in mature N 2 -fixing nodules [ 36 ]. Two of these eight NPFs, LjNPF8.6 and LjNPF3.1, were studied in depth [ 38 , 39 ]. LjNPF8.6 , whose expression is strongly induced in nodules compared to roots, is the first NPF for which a specific and positive role on nodule functioning has been shown [ 38 ].…”
Section: Npfs Playing a Role In Nodule Functioningmentioning
confidence: 99%
“…In addition, after inoculation of Ljnpf8.6 mutants by Mesorhizobium loti , an increase in nodular superoxide content in the nodules accompanied by a reduction in N-fixation activity was observed with an accumulation of anthocyanin in stems and roots [ 38 ]. Anthocyanin accumulation in stems has been reported as a phenotype associated with nitrogen starvation condition associated with impaired nodule function or lack of nodulation ([ 39 ] and references therein). These observations suggest that LjNPF8.6 plays a role in the control of nodule functioning rather than in development.…”
Section: Npfs Playing a Role In Nodule Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…CoNPF3.1 (40839_c0_g1) was annotated to nitrate transporter1/peptide transporter (NPF) family, and it has been described as transmembrane transporter, gibberellic acid homeostasis and nitrate assimilation in Arabidopsis thaliana [21].. It may be improve development of bud and growth of root [22].…”
Section: Coexpression Network Analysis With Wgcnamentioning
confidence: 99%